Bimbingan Rohani Bagi Pemuda Melalui Gerakan Cinta Alkitab - Rinaldus Tanduklangi (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Youth is the hope of the church which should be one of the main concerns in the church. As the future of the church, youth need to be prepared so that they are able to face the challenges of the church in the future. In order to prepare the youth, the practical effort that can be done by the church is spiritual guidance. Spiritual guidance is a Bible-centered coaching and teaching activity. Spiritual guidance is important, considering today's youth are vulnerable and very easily influenced. Starting from this understanding, in carrying out the task of the Tri Dharma of Higher Education, namely Community Service, the author chose church youth as the target of implementing these Community Service activities. The form of service carried out is spiritual guidance for youth through the love of the Bible movement. In carrying out these activities there are three main stages that the author takes starting from the planning, implementation and evaluation stages. Specifically at the implementation stage, the authors apply various methods that involve youth actively participating. As a result of these activities, young people have an awareness of their responsibilities as the baton of the church so that they need to prepare themselves by reading and loving the Bible as a source of truth and Christian teaching.